The voluntary legal fact - De Espanés, Luis Moisset (2007)
The present article began approaching the importance of the will within the Civil Law, later treats the legal will, afterwards follows with theautonomy of the will in the present, finally develops each one of the elements of the voluntary fact as they are the discernment, the intensityand the freedom, its characteristics and restrictions